2018
DOI: 10.1097/md.0000000000012759
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the pay-for-performance program on lower extremity amputations in patients with diabetes in Taiwan

Abstract: Patients with diabetes are at a high risk of lower extremity amputations and may have a reduced life expectancy. Taiwan has implemented a diabetes pay-for-performance (P4P) program providing team care to improve the control of disease and avoid subsequent complications. Few studies investigated the effects of adopting a nationalized policy to decrease amputation risk in diabetes previously. Our study aimed to analyze the impact of the P4P programs on the incidence of lower extremity amputations in Taiwanese pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 29 publications
(37 reference statements)
2
24
0
3
Order By: Relevance
“…The type of diabetes, ethnicities, age distribution, comorbidities and the utility of medical resource may all attribute to the difference. Sheen et al reported a similar decrease of LEAs in patients with diabetes between 1998 and 2007 (3.79 and 2.27/1000/year) 19. Although the authors suggested the impact of pay-for-performance programme in Taiwan, this conclusion may be over-reaching because only 12% coverage rate of that programme for patients with diabetes at that time 26.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The type of diabetes, ethnicities, age distribution, comorbidities and the utility of medical resource may all attribute to the difference. Sheen et al reported a similar decrease of LEAs in patients with diabetes between 1998 and 2007 (3.79 and 2.27/1000/year) 19. Although the authors suggested the impact of pay-for-performance programme in Taiwan, this conclusion may be over-reaching because only 12% coverage rate of that programme for patients with diabetes at that time 26.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the robust and comprehensive nature of the Taiwan National Health System database, we were able to report the in-hospital foot diseases characteristics between years 2000 and 2009 18. The annual incidence of diabetes-related LEA in Taiwan between 1998 and 2007 was 3.79 and 2.27/1000/year, respectively 19…”
Section: Introductionmentioning
confidence: 99%
“…Research Database (NHIRD, Taiwan). 41,45 However, in all three cases, different subpopulations were included in the studies, and different risk factors were analysed in each of the publications.…”
Section: Re Sultsmentioning
confidence: 99%
“…The characteristics of all 31 articles, which were published between 1995 and 2019, are shown in Table 1. Six studies were performed in China, 32,33,36,39,51,54 five in the United States, 30,34,44,49,52 three in Taiwan, 41,45,46 two in the UK, 26,35 Denmark 28,29 and Saudi Arabia, 25,37 and one study each in Australia, 27 Austria, 40 Finland, 48 Ghana, 43 Italy, 47 New Zealand, 42 Pakistan, 53 Republic of Nauru 38 and Singapore. 50 In addition, two multinational studies were included, one of which was conducted in Europe (UK, Switzerland, Germany, in which the proportion of female patients was as low as 2.6%.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation